DETERMINATION OF ATTORNEY SERVICE FEES AT THE OFFICE OF LEGAL ADVISER MR. PHILIPUS FERNANDEZ IN KUPANG CITY - Karolus Belmo; Marianus Saldanha Neno (Jurnal Ekonomi, 2022)
In order for business activities to run well and maximize, it is necessary to make several determinations and one of them is tariff setting. One of the suitable pricing methods used in the service sector is the time and material pricing method. The main problem in this study is that the determination of consulting fees is relatively low and does not take into account the costs incurred to facilitate work activities. The type of research used in this research is descriptive analysis in the form of a case study. The data collection methods used in this research are interviews, document collection and observation. The data analysis technique used in this research is the time and material pricing method. The results showed that the calculation of raw material costs, direct labor costs and factory overhead costs was lower than the calculations made by researchers where according to the Office of Legal Counsel Mr. Philipus Fernandez, raw material costs were IDR 5,365,000, direct labor costs were IDR 200,040,000, fixed factory overhead costs were IDR 360,000. 000, and variable factory overhead costs are not taken into account, while according to researchers, raw material costs amounted to Rp 5,605,000, direct labor costs amounted to Rp 200,940,000, fixed factory overhead costs amounted to Rp 483,673,925, and variable factory overhead costs amounted to Rp 54,178,000, so there is a difference in the calculation between the Office of Legal Counsel Mr. Philipus Fernandez and researchers.